Assessing the revenue efficiency of domestic and foreign Islamic Banks:empirical evidence from Malaysia - Fadzlan Sufian; Fakarudin Kamarudin; Nor Halida Haziaton Mohd Noor (Penerbit Universiti Kebangsaan Malaysia, 2013)
The present paper provides new empirical evidence regarding revenue efficiency in the Malaysian Islamic banking sector during the period from 2006 to 2010. The sample is comprised of 17 domestic and foreign Islamic banks. The Data Envelopment Analysis (DEA) method is employed to compute the revenue efficiency levels. The results indicate that the domestic Islamic banks exhibit lower revenue efficiency levels compared to foreign counterparts. In addition,the empirical findings suggest that the foreign Islamic banks exhibit higher efficiency levels for all three efficiency measures and are consistent with the global advantage theory. In essence, revenue efficiency seems to play the main role in lower or higher profit efficiency levels. The findings of the present study are expected to be relevant to regulators and policymakers, the Islamic banking industry and investors; and contribute significantly to existing knowledge on the operating performance of the Malaysian Islamic banking sector.